Sticky Advice for Research Students - McGann, Sarah; Milech, Barbara (Sense Publishers, 2013)
The sticky advice for doctoral students reproduced on the following page represents our sense of the collaboration between doctoral student and supervisor when all goes well. For Sarah, it represents her sense that the doctoral student moves from a position of learning to teaching – the sticky notes come from a presentation she gave to current doctoral students in her department shortly after graduation.